Is Cord Blood Bilirubin Level a Reliable Predictor for Developing Significant Hyperbilirubinemia? - Aktas, Selma; Dogan, Caner; Okmen, Zeynep Hazıroglu; Gulec, Seda Geylani (American Journal of Perinatology, 2019)
Objective We aimed to investigate whether cord blood bilirubin (CBB) level could be used to identify the newborns at a high risk of developing hyperbilirubinemia.Study Design Total and direct serum bilirubin level were evaluated from umbilical cord blood of newborns. We checked blood groups and Rh status of all mothers and determined blood groups and direct Coombs test (DC) of newborns born to mothers whose blood group was O type or Rh negative to determine the maternal–fetal blood group or Rh incompatibility.Results A total of 418 newborns were included, and phototherapy (PT) was required in 17 newborns. The cutoff value of CBB for predicting the occurrence of significant hyperbilirubinemia requiring PT was 1.67 mg/dL, with a sensitivity of 82% and specificity of 99%. The mean CBB level in babies receiving PT was 2.4 ± 0.9 mg/dL. When blood group, CBB level, DC, gender, and mode of delivery were assigned as possible risk factors, multıvariate analysis showed ABO, Rh incompatibility, and CBB level increased the risk of PT requirement.Conclusion CBB could be useful to determine newborns at a risk of developing hyperbilirubinemia and prevent developing severe complications due to delay in diagnosis.
Keywords: cord blood bilirubin; hyperbilirubinemia; neonate; phototherapy